Hardware/software co-verification of USB3.0 IP core under PowerPC architecture - Deng Jiawei; Zhang Meijuan; Wang Qi; Yang Chuwei; Ying Lingkai (Dianzi Jishu Yingyong, 2022)
With the increasing requirement of transmission rate of USB,the traditional PowerPC processor based on the USB2.0 can not meeet the requirements of high speed and large-capacity transmission.The paper presents a solution of USB 3.0 base on PowerPC processor architecture. By comparing USB3.0 and USB2.0, USB3.0 has higher transmission rate.By cooperating with the high preformance PowerPC processor, the transfer capability of the USB controller is improved significantly, and ther PowerPC computing resources are fully utilized.This paper describes a programme of USB3.0 IP core based on the PowerPC architecture. Finally the the method of hardware/softeware cooperative verification is used to verfiy the feasibility of the design,which lays a technical foundation of subsequent chip design and verification.